Faktor-Faktor yang Mempengaruhi Kepatuhan Ibu dalam Pemanfaatan Posyandu di Wilayah Kerja Puskesmas Menteng Kota Palangka Raya - Nita Theresia; Rikiy Rikiy (Jurnal Surya Medika (JSM), 2020)
Central Kalimantan achievement rate in several public health indicators is below the national achievement such as Td2+ immunization coverage (46.2%), postpartum maternity service coverage (76.75%), complete basic immunization coverage (87.3%), and prevalence of lean children (10.6%) and stunting (39%). Utilization of health services, especially posyandu, is still not optimal, which has an impact on the number of children under five suffering from malnutrition and the coverage of several posyandu activities that are still below the national achievement rate. The research design used was observational analytic using a cross-sectional approach. The subjects in this study were all mothers who came to posyandu who were selected by the total sampling technique. From the results of univariate analysis, most mothers who actively use services at posyandu are mothers who are in the age range of 20-35 years, amounting to 55%, the last high school education is as much as 40%, mothers who have toddlers and not working 85%, affordable distance 90%, and non-routine visits to posyandu 87.5%. Based on bivariate analysis, no independent variables (age, education, occupation, and distance) were found which showed the influence on the use of posyandu services.